Fire Resistance of RC Frame in Case of Post Earthquake Fire - Lazarov, Ljupco; Cvetkovska, Meri; Todorov, Koce (Multi-Science Publishing, 2013)
Fire following an earthquake is an important factor causing damage to buildings and life-line structures. Therefore, besides satisfying structural design requirements for normal loads, such as dead and live loads including the seismic hazard, buildings should also be designed to withstand the fire following earthquakes for a certain minimum duration as required for a desired level of performance. The behavior of a particular reinforced concrete structure that was fire exposed after seismic action is presented in this paper. The seismic response of the structure is evaluated using a pushover analysis, while the displacement demand under the corresponding seismic event is determined using the recommendations implemented in Eurocode 8.
Keywords: fire, earthquake, fire resistance, stress-strain analysis, pushover analysis